Penyuluhan Baby Gym untuk Meningkatkan Motorik dan Kesehatan Bayi pada Komunitas Kelas Ibu Bayi Balita di Puskesmas Kendalsari Kota Malang - Yafi’ Helmi Jauhari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Background: Infants aged 2 months have begun to learn body movements in the form of gross motor skills. Starting with kicking movements, straightening the hands of sideways movements and then on the stomach until at the age of 1 year the baby can walk independently. Gross motor can develop faster and better when there is stimulus from the surrounding environment. Baby gym can provide a stimulus for gross motor development. Baby gym exercises done with the person closest to the baby will be better for the baby's emotional security. Objective: Providing counseling and practice in mother and baby classes at the kendalsari health center makes mothers who have babies under 1 year old and who will have a baby can apply it at home to train their children's gross motor skills. Methods: the method used in this counseling is to provide leaflets and then education and practice. Giving some questions on the pretest and postest to find out the picture of knowledge in mothers. Results: from this activity an increased understanding of baby gym procedures and their benefits was obtained.